The effectiveness of web advertising in influencing the people in Klang Valley towards Visit Malaysia year 2007 / Razilah Jalil - Jalil, Razilah (Faculty of Business and Management, 2007)
This research is conduct to carry out The Effectiveness of Web Advertising in influencing the people in Klang Valley towards Visit Malaysia Year 2007. The main objective is to measure the level of people awareness about Tourism Malaysia website especially during Visit Malaysia Year 2007. As we know, Tourism Malaysia is an organization under government who are responsible to promote Malaysia all around the world. Our government has been spend a lot of money because realizes that tourism industry has potential to increase government revenue after oil industry.